EXAMINING GENDER DIFFERENCES IN PERCEIVED PARENTING STYLES OF ADOLESCENTS IN KLANG VALLEY: A QUANTITATIVE STUDY - Ho Meng Chuan; Jas Laile Suzana Jaafar, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The present research examined gender differences in perceived parenting styles of adolescents. Sample comprised of 579 adolescents with 316 females and 263 males and was recruited from 6 public schools in Klang Valley. Parental Authority Questionnaire was used for the study. Study reported that both male and females perceived their parents (paternal and maternal) as authoritative, however, there is no significant differences of gender differences in perceived paternal and maternal parenting styles. Findings suggested that Baumrind’s parenting typology is applicable in collectivist countries like Malaysia. Therefore, it is implicated that there are more similarities than differences in results between Western countries and Malaysia.